1998
DOI: 10.1093/carcin/19.6.1007
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition by 1'-acetoxychavicol acetate of lipopolysaccharide- and interferon-gamma-induced nitric oxide production through suppression of inducible nitric oxide synthase gene expression in RAW264 cells

Abstract: Although nitric oxide (NO) is an important biological mediator, excessive production in inflammation is thought to be a causative factor of cellular injury and cancer in the long term. In the present study the effects of 1'-acetoxychavicol acetate (ACA), which has anticarcinogenic properties, on NO production in murine macrophage cell line RAW264 cells stimulated with lipopolysaccharide or interferon-gamma were examined. ACA suppressed NO production dose dependently with an IC50 of 160 ng/ml (680 nM). The decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 42 publications
2
21
0
Order By: Relevance
“…The down-regulation of COX-2 by ACA is consistent with a previous report that showed suppression of COX-2 expression induced by LPS/IFN-␥ in mouse macrophages (69). Our results may also explain the down-regulation of inducible NO synthase expression (14), which is also regulated by NF-B.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The down-regulation of COX-2 by ACA is consistent with a previous report that showed suppression of COX-2 expression induced by LPS/IFN-␥ in mouse macrophages (69). Our results may also explain the down-regulation of inducible NO synthase expression (14), which is also regulated by NF-B.…”
Section: Discussionsupporting
confidence: 93%
“…Protein tyrosine phosphorylation and reduction of cellular sulfhydryl groups have been implicated in ACA-induced apoptosis (12). Still other reports have indicated that ACA has antioxidant and anti-inflammatory activities (13,14), inhibits xanthine oxidase (4), and suppresses inducible NO synthase gene expression (14). How ACA mediates antitumor activities is not well understood.…”
Section: Identification Of a Novel Blocker Of Ib␣ Kinase That Enhancementioning
confidence: 99%
“…One such nonsteroidal anti-inflammatory drug is ibuprofen, which reduces iNOS activity in rat alveolar macrophage cultures stimulated by lipopolysaccharide and IFN-␥ (44). Some natural products including resveratrol (45), carnosol (46), and 1Ј-acetoxychavicol acetate (47), have been shown to inhibit iNOS gene expression and to reduce its activity. The mechanism(s) for their ability to elicit dual inhibitory effects have not been determined; however, the influence of these natural products on iNOS gene expression may be due, at least in part, to inhibition of nuclear factor B activation (48).…”
Section: Discussionmentioning
confidence: 99%
“…DISCUSSION ACA has been found to be a potential inhibitor of tumorpromotion in an in vitro Epstein-Barr virus activation test Re-80 1 18 10 (55.6) 2.0 ± 3.1 6.8 ± 18.0 * 12 (66.7) 1.7 ± 1.9 4.2 ± 11.7 15 (83.3) 3.7 ± 3.9 5.5 ± 15.4 Re-80 0.4 18 6 (33.3) 0.9 ± 1.9 2.3 ± 3.4 * 9 (50.0) 1.6 ± 3.3 8.7 ± 18.5 12 (66.7) 2.4 ± 4.0 6.4 ± 15.1 Am-580 20 18 3 (16.7) 0.2 ± 0.4 0.2 ± 0.1 15 (83.3) 3.1 ± 2.6 9.9 ± 5.3 15 (83.3) 3.3 ± 2.8 4.4 ± 5.2 Am-580 5 18 8 (44.4) 0.7 ± 1.0 0.4 ± 0.4 15 (83.3) 3.3 ± 3.1 5.5 ± 5.3 16 (88.9) 4.1 ± 3.8 4.6 ± 8.5 Am-55P 20 18 7 (38.9) 1.2 ± 2.6 6.9 ± 17.1 8 (44.4) 2.2 ± 3.6 2.2 ± 7.7 12 (66.7) 3.4 ± 4.8 3.8 ± 10.8 ACA 100 18 12 (66.7) 1.9 ± 2.6 0.7 ± 0.8 10 (55.6) 1.4 ± 1.9 6.1 ± 11.5 16 (88.9) 3.3 ± 3.0 2.9 ± 8.3 All-trans-retinoic acid 10 17 10 (58.8) 1.4 ± 2.1 0.5 ± 0.9 10 (58.8) 1.1 ± 1.4 3.1 ± 7.5 14 (82.4) 2.5 ± 2.6 1. for screening of edible plants from Thailand (Kondo et al, 1993;Murakami et al, 1995), and ACA showed chemopreventive or anti-tumor promotion activities in vivo studies in rats or mice treated with chemical carcinogens (Tanaka and Mori, 1995;Murakami et al, 1996;Ohnishi et al, 1996;Nakamura et al, 1998;Tanaka et al, 1997aTanaka et al, , 1997b. ACA inhibits xanthine oxidase activity and nitric oxide production (Noro et al, 1988;Ohata et al, 1998) involved in tumorigenesis (Pence and Reiners, 1987;Cerutti, 1994 chromosomal change, and activation of cytoplasmic signal transduction pathways related to cell growth (Cerutti, 1994). For this reason, it is to be expected that ACA would inhibit all stages of tumor development including initiation, promotion and progression.…”
Section: Incidences and Multiplicities Of Tumors In Different Organs mentioning
confidence: 99%
“…It has been shown to inhibit the activity of xanthine oxidases, including a nitric oxide (NO) synthase (Noro et al, 1998;Ohata et al, 1998). Reactive oxygen species are known to participate in all stages of carcinogenesis including initiation, promotion, and progression (Pence and Reiners, 1987;Cerutti, 1994), and therefore, xanthine oxidase inhibitors are expected to be chemopreventors.…”
Section: Introductionmentioning
confidence: 99%